Otwarcie edukacji międzykulturowej na krytyczną recepcję pedagogicznego przesłania religii w kontekście pluralizmu światopoglądowego - Marek Rembierz (Społeczeństwo, 2022)
The criticism regarding the ideology of multiculturalism has recently become more intensive. However, if you look at the critical debate among Western societies on the undesired and destructive results of the ideology of multiculturalism from the point of view of Polish tradition and intellectual research, it seems that the Polish reflection concerning various aspects of the experience of multiculturalism and formation of multicultural relationship might, in crucial points, appear deeper and more intellectually mature than some of the Western propositions that are perceived as the leading ideas and strategies.